ABO‐Incompatible Adult Living Donor Liver Transplantation Under the Desensitization Protocol With Rituximab. Issue 1 (15th September 2015) - Song, G.‐W.; Lee, S.‐G.; Hwang, S.; Kim, K.‐H.; Ahn, C.‐S.; Moon, D.‐B.; Ha, T.‐Y.; Jung, D.‐H.; Park, G.‐C.; Kim, W.‐J.; Sin, M.‐H.; Yoon, Y.‐I.; et al.
Abstract : ABO incompatibility is no longer considered a contraindication for adult living donor liver transplantation (ALDLT) due to various strategies to overcome the ABO blood group barrier. We report the largest single‐center experience of ABO‐incompatible (ABOi) ALDLT in 235 adult patients. The desensitization protocol included a single dose of rituximab and total plasma exchange. In addition, local graft infusion therapy, cyclophosphamide, or splenectomy was used for a certain time period, but these treatments were eventually discontinued due to adverse events. There were three cases (1.3%) of in‐hospital mortality. The cumulative 3‐year graft and patient survival rates were 89.2% and 92.3%, respectively, and were comparable to those of the ABO‐compatible group (n = 1301). Despite promising survival outcomes, 17 patients (7.2%) experienced antibody‐mediated rejection that manifested as diffuse intrahepatic biliary stricture; six cases required retransplantation, and three patients died. ABOi ALDLT is a feasible method for expanding a living liver donor pool, but the efficacy of the desensitization protocol in targeting B cell immunity should be optimized. Abstract : This article presents the clinical results of ABO‐incompatible adult living donor liver transplantation in a single institution.